Aplicação do Modelo Calgary para avaliação de famílias de idosos hospitalizados sob cuidados paliativos - Duarte, Marcella Costa Souto (2015)
This thesis is constituted by three articles, one theoretical, entitled Scientific Production about the elderly person in palliative care: a bibliometric study and two originals: Structural evaluation, developmental, and functional of families of elderly patients with cancer in palliative care; and Family Evaluation of elderly patients with Brain Vascular Accident in palliative care. Objective: to analyze the structure, the development and functionality of elderly patients family without therapeutic possibilities of cure in palliative care in the light of Calgary Model of Family Evaluation (CMFE). Method: The proposed search is a field research, of qualitative nature. The study was performed in a hospital, located in the city of João Pessoa, capital of the State of Paraíba. The investigation sample was composed by ten families, each one represented by the patient under palliative care and one family companion. The project was appreciated and approved by the Committee of Ethics in Research of the University Hospital Lauro Wanderley, from the Federal University of Paraíba (CER/UHLW), according to approval certificate with registration CAAE, number 33261114.1.0000.5183. Data were collected in the period from August to September 2014. For data collection was utilized the interview technique and genogram and eco-map instruments, that are utilized in CMFE. Empirical material was analyzed qualitatively in the light of CMFE. Results: From the ten families selected for the study, five had a common point, in other words, patients with cancer diagnosis, and five, with Brain Vascular Accident (BVA) diagnosis. For that, this material enabled the construction of two articles. The application of the referred model allowed identifying in the search with the family of elderly patients with cancer that two of them preserved the nuclear structure. The families presented low education level and financial difficulties. Regarding the network of social support, most mentioned relatives, friends and church. Two referred to have family relation with conflicts and limited social contact. The family caregivers are female. The article with the patients’ family with BVA allowed identifying that the five families that preserved nuclear structure, presented low education level and financial difficulties. They had as social support network relatives, friends and church. All of them referred to have family relation with conflicts. Conclusion: Family system and social, cultural contexts where the elderly patients with cancer and BVA families in palliative care participants in the research are inserted, can influence the way to direct these care.